The content of heavy metals in the aerial parts of the common nettle and sun spurge from Oštrelj (municipality of Bor): A contribution to the examinations of plant biomonitoring and phytoremediation potentials - Zoran O. Stevanović; Slađana Č. Alagić; Snežana B. Tošić (Zaštita Materijala)
In this paper, the content of heavy metals Cu, Cd, Zn, Ni, Pb, and As in the aerial parts of the common nettle and sun spurge from the territory of rural settlement Oštrelj (4-5 km far from the mining metallurgical complex in Bor, Serbia) was investigated in terms of preliminary estimation of their biomonitoring and phytoremediation potentials. The most abundant detected metal in both plant species was Cu, with the notification that its concentrations reached even phytotoxic levels. Similar situation was found also in the case of As, and Ni in the sun spurge, which showed to be much efficient in metal accumulation than common nettle. Since both investigated plants showed as tolerant species regarding certain metals (reflecting at the same time the existence of contamination in these cases), it can be concluded that their application in biomonitoring of polluted areas is possible, whereas, when the application in phytoextraction (as one of the most effective phytoremediation methods) is the matter of interest, it can be said that only sun spurge showed some potential in this regard, especially in the case of Cu.